Upper blepharoplasty and eyebrow position. (4th May 2017) - Kashkouli, Mohsen Bahmani; AbolfathZadeh, Navid; Abdolalizadeh, Parya; Sianati, Hamed; Karimi, Nasser
ABSTRACT: Introduction : Most of the subjects seeking for upper blepharoplasty procedure have a component of eyebrow ptosis with or without asymmetry. On the other hand, there have been different reports regarding the effect of upper blepharoplasty on postoperative eyebrow position in the past two decades. The aims of this review are to find out the reasons for eyebrow asymmetry before and evaluate the eyebrow position after upper blepharoplasty procedure. Areas covered : PubMed literature search was performed using the keywords 'upper blepharoplasty', 'eyebrow', 'eyebrow ptosis', and 'eyebrow asymmetry'. There were more than 1030 articles from which 138 were relatively covering the subject of upper blepharoplasty and eyebrow together. Abstract were read and 83 articles were selected for full text review. Finally, 76 English language articles were included and then reviewed for the aims of this study. There were some reports on no change of eyebrow position and some on descend of eyebrow after upper blepharoplasty procedure. Expert commentary : Lateral hooding of mild eyebrow ptosis could be addressed through a wider skin excision of the lateral blepharoplasty. However, a significant preoperative eyebrow ptosis or asymmetry should be addressed by the mean of simultaneous eyebrow lifting.